IDENTIFIKASI LARVA NYAMUK SEBAGAI VEKTOR PENYAKIT DI TEMPAT PENAMPUNGAN AIR RUMAH SAKIT UMUM DAERAH ABUNAWAS KOTA KENDARI - sultanaulya muhammad; Apriyanto Apriyanto; Savirah Hardiyanti (Jurnal Analis Kesehatan Kendari, 2022)
Mosquito larvae are one of the stages of development of mosquitoes. Mosquitoes are the main vector insects that cause various important tropical diseases in Indonesia such as malaria, DHF, chikungunya, lymphatic filariasis and Japanese encephalitis. Mosquitoes are one type of insect that belongs to the order Diptera and the Culicidae Family. Infectious diseases caused by mosquito vectors (vector borne disease) such as dengue hemorrhagic fever (DHF), malaria, filariasis (elephantiasis), and Japanese B. Enchephalitis, are still a public health problem in the world including Indonesia. This study aims to find out how to identify mosquito larvae as vectors of disease in water reservoirs located in the Abunawas General Hospital, Kendari City. The type of research used is quantitative. The sample in this study was mosquito larvae. The results showed there were 7 reservoirs that were larva positive, namely Aedes Sp. and Culex Sp. These results state that this region can be at risk of disease transmission through mosquito vectors with high mosquito larvae densities. Key words: Mosquito larvae, vector of disease